Evaluasi hambatan waktu penyediaan dokumen rekam medis elektronik di RS Murni Teguh Medan - Sri Lestari Ramadhani Nasution; Hafiz Hawari Siregar; Maco Chan Adnan; Ermi Girsang (Jurnal Penelitian Pendidikan IPA, 2023)
The impact of errors in storing medical records causes delays for officers in searching for medical record documents so that services at the polyclinic are hampered. It is necessary to control the incidence of incorrect insertion of medical record documents so that the incidence of incorrect insertion of medical record documents can be reduced. Electronic Medical Record (RME) is a form of health information service that is computerized and recorded. Health service facilities that implement RME in an effort to improve the quality and quality of services. This research is a qualitative research, case study design which aims to evaluate the timing of providing electronic medical record documents for outpatients at Murni Teguh Hospital. Determination of research subjects using purposive sampling technique. The research subjects consisted of the Director of Murni Teguh Hospital, the head of the Medical Record Installation as the main informant, the Patient Registration Officer, and 3 medical record staff as triangulation informants. In collecting data, researchers conducted in-depth interviews, direct observation and document studies. Data analysis was carried out using interactive models, data reduction processes, verification and drawing conclusions. In this study, it was found that the time required to provide electronic medical record documents for outpatients at Murni Teguh Hospital was a minimum of 4 minutes, a maximum time of 9 minutes with an average time needed to provide electronic medical record documents was 6.6 minutes. Obstacles encountered are errors during use, as well as HR who still do not understand the use of electronic medical record systems. By providing electronic medical record documents, the work of the patient medical record department becomes more efficient, makes it easier for officers to search for patient medical records and the benefits that patients get are shorter waiting times.